2021
DOI: 10.3390/microorganisms9122586
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manure Application on the Soil Bacterial Microbiome in Integrated Crop-Livestock Farms in Maryland

Abstract: As a traditional agricultural system, integrated crop-livestock farms (ICLFs) involve the production of animals and crops in a shared environment. The ICLFs in the mid-Atlantic region of the United States practice sustainable manure aging or composting processes to provide an on-farm source of soil amendment for use as natural fertilizer and soil conditioner for crop production. However, crop fertilization by soil incorporation of aged manure or compost may introduce different microbes and alter the soil micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Organic N fertilizers increased Proteobacteria and Bacteroidetes, but decreased Acidobacteria, Chloroflexi, and Gemmatimonadetes. Similar changes in the relative abundances of these phyla have been identified through on-farm surveys of manure or compost treated soils (48).…”
Section: Organic Fertilization Affected Bacterial and Fungal Communit...supporting
confidence: 66%
“…Organic N fertilizers increased Proteobacteria and Bacteroidetes, but decreased Acidobacteria, Chloroflexi, and Gemmatimonadetes. Similar changes in the relative abundances of these phyla have been identified through on-farm surveys of manure or compost treated soils (48).…”
Section: Organic Fertilization Affected Bacterial and Fungal Communit...supporting
confidence: 66%
“…This was to be expected, because of nutrient sources, such as sheep excrement and grass remnants, which are rich in organic carbon, organic matter, carbonates and nitrogen (Wan et al, 2021). Moreover, several studies have shown that cover crops improve C, N and P cycling by retaining moisture, and by increasing soil microbiota diversity (Kim et al, 2020); and animal manures can promote differential growth of prokaryotic microorganisms thus increasing soil fertility (Gómez‐Tenorio et al, 2021; Peng et al, 2021; Wan et al, 2021). In contrast, in the Monoc the main source of organic matter is the leaf litter of C. dodecandra trees.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation is that the higher richness, evenness and Shannon diversity in Silvo, causes the abundance of all orders to be relatively low. Another unexpected result was the low abundance of Enterobacteriales in the Silvo samples (0%–0.28%), because sheep excrement contains around 40% of this bacterial order (Shabana et al, 2021), and usually prokaryotic communities in the soil are enriched in it when manure is applied (Peng et al, 2021). It may be that these soils have characteristics that somehow inhibit the proliferation of this order, since similar results were obtained in a previous analysis of Yucatan soils (Estrada‐Medina et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying organic fertilizer is an important measure of soil improvement and soil fertility enhancement. Organic fertilizer can effectively change the species and quantity of soil microorganisms and thereby affect the structure and spatial distribution of the soil bacterial community [5][6][7][8]. Soil bacterial diversity and community structure can sensitively reflect soil quality, soil fertility, and soil health [9,10].…”
Section: Introductionmentioning
confidence: 99%